(untitled) (Research, Society and Development, 2021)
Objectives: to identify the characteristics of the organization of hospital work, from the perspective of nursing workers, and to analyze the repercussions of the organization of hospital work on the subjectivity of these workers. Method: qualitative, descriptive study whose participants were 22 nursing technicians and 12 nurses from a medium-sized hospital unit in the southwest region of Bahia. The collection was carried out through semi-structured interviews and the information was treated in the light of the thematic content analysis technique. Result: it was found that the organization of work makes the worker multipurpose and multifunctional. There is a significant gap between prescribed work and real work, which predisposes workers to suffering. It was found that there is precarious work and technical division of labor that causes class conflicts. Conclusion: The configuration of the work organization predisposes more to the psychophysical suffering of the worker than it contributes to protect the subjectivity of the professional group.